Resilience in patients and spouses faced with malignant melanoma. A qualitative longitudinal study. (28th July 2014) - Engeli, L.; Moergeli, H.; Binder, M.; Drabe, N.; Meier, C.; Buechi, S.; Dummer, R.; Jenewein, J.
Abstract : Life‐threatening diseases like malignant tumours are associated with considerable existential distress. Little is known about the factors that promote resilience within these individuals. This longitudinal qualitative partner study aimed to analyse resilience as per Antonovsky's sense of coherence. Eight patients with malignant melanoma and their partners were interviewed. They were asked about their coping strategies, attitudes towards the meaning of life and their cancer, and comprehension of what is happening to them. The questions were asked shortly after their diagnosis was made and 6 months later. All interviews were audio‐taped and later transcribed and analysed according to the method of qualitative content analysis described by P. Mayring. At baseline, the majority of statements made (261; patients = 141/spouses = 120) related to coping/manageability of disease, with only 26 statements (patients = 15/spouses = 11) related to meaning and 127 (patients = 64/spouses = 63) to comprehension . There were no significant differences between the responses of patients and their partners and no significant changes in the number of statements during the 6‐month interview. The most significant theme that emerged was manageability of disease, with distraction the most commonly utilised coping skill. The comprehension and meaning themes were far less prevalent. Hence, support should focus on disease and situational manageability.